Post-Covid-19 Acute Disseminated Encephalomyelitis (ADEM) in a 27-year-old girl: Case Report - AGBA Léhleng; SORO Donissongui; Awissoba AWIDINA-AMA; YAÏCHE Hugo; HEINZLEF Olivier (Journal of Neurological Research And Therapy, 2022)
Acute disseminated encephalomyelitis (ADEM) is a monophasic, multifocal, demyelinating, autoimmune disease that affects the central nervous system (CNS). It usually occurs after a systemic infection, usually viral, including certain coronavirus infections. A 27-year-old girl presented with complaints of left interscapular pain, paresthesias and weakness in the ipsilateral upper limb. These symptoms followed paresthesias on the fingertips of her right hand the day before her admission. she was treated two weeks earlier for pneumonia with COVID-19. Her clinical pattern resulted in a moderate weakness of the left limbs associated with tactil and algic hypoesthesia in the lower left limb ascending until the C4 level in the left side. Magnetic resonance imaging (MRI) of the brain and spinal cord showed diffuse spontaneous hypersignals on fluid-attenuated inversion recovery (FLAIR) images at the cerebral level and on T2-weighted images at the spinal level. These imaging lesions coupled with the medical history of a recent COVID-19 infection led to the diagnosis of acute disseminated encephalomyelitis (ADEM) post covid-19. The clinical condition improved rapidly with intravenous (IV) corticosteroid therapy and IV immunoglobulin combined with physiotherapy. ADEM is a demyelinating autoimmune disease which is increasingly reported during this current corona virus pandemic.
Keywords: ADEM